How a mandatory activation program reduces unemployment durations: the effects of distance - Brian Krogh Graversen; Jan C. van Ours (Institute for the Study of Labor (IZA), 2009)
In an experimental setting some Danish unemployed workers were assigned to an activation program while others were not. Unemployed who were assigned to the activation program found a job more quickly. We show that the activation effect increases with the distance between the place of residence of the unemployed worker and the place where the activation took place. We also find that the quality of the post-unemployment jobs was not affected by the activation program. Both findings confirm that activation programs mainly work because they are compulsory and unemployed don't like them.
urn:nbn:de:101:1-20090330128
Keywords: C41; H55; J64; J65; 330; Unemployment insurance; unemployment duration; experiment; activation programs; Arbeitslosigkeit; Dauer; Arbeitsmarktpolitik; Wirkungsanalyse; Berufliche Integration; Wohnstandort; Entfernung; Test; Dänemark